Revealing the complexity of community-campus interactions - Nichols, Naomi Elizabeth (Canadian Journal of Higher Education, 2014)
In this paper, four qualitative case studies capture the complex interplay between the social and structural relations that shape community - academic partnerships. Collaborations begin as relationships among people. They are sustained by institutional structures that recognize and support these relationships. Productive collaborations centralize reciprocity, flexibility, and relationship building between individuals and institutions. Our findings also indicate a synergistic interaction between collaborative processes and outcomes: an equitable process supports the development of mutually beneficial outcomes, and the ability to sustain a collaborative process requires substantive progress towards shared change goals.